2014
DOI: 10.1097/med.0000000000000095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin on weight loss

Abstract: Metformin induces modest weight loss in overweight and obese individuals at risk for diabetes. A more detailed understanding of how metformin induces weight loss will likely lead to optimal co-prescription of lifestyle modification with pharmacology for the treatment of obesity independent of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
146
1
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(171 citation statements)
references
References 43 publications
6
146
1
14
Order By: Relevance
“…Despite the known glucose-lowering effects of metformin, more recent clinical interest lies in its potential as a weight loss drug based primarily on its ability to stimulate a reduction in food intake. In addition to appetite suppression, metformin improves leptin sensitivity, changes gastrointestinal physiology, and regulates fat oxidation and storage [11]. Clinical studies revealed that metformin treatment of oligo-teratoasthenozoospermic men with metabolic syndrome obtained satisfactory effects, including significant reductions in insulin and sex-hormone-binding globulin levels, increased serum androgen levels, and a consequent improvement in semen characteristics [19].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite the known glucose-lowering effects of metformin, more recent clinical interest lies in its potential as a weight loss drug based primarily on its ability to stimulate a reduction in food intake. In addition to appetite suppression, metformin improves leptin sensitivity, changes gastrointestinal physiology, and regulates fat oxidation and storage [11]. Clinical studies revealed that metformin treatment of oligo-teratoasthenozoospermic men with metabolic syndrome obtained satisfactory effects, including significant reductions in insulin and sex-hormone-binding globulin levels, increased serum androgen levels, and a consequent improvement in semen characteristics [19].…”
Section: Discussionmentioning
confidence: 96%
“…Long-term follow-up from the Diabetes Prevention Program demonstrated that metformin produced durable weight loss in several ways, with decreased food intake shown to be the primary mechanism [11]. Clinical trials showed that the mean total and free testosterone levels increased significantly after metformin treatment in men with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Some suggested that metformin can induce hypothalamic leptin receptor expression and increase central leptin sensitivity which then inhibits food intake [17]. Others suggested that changed gastrointestinal physiology and circadian rhythm by metformin could also affect food intake, fat oxidation and storage [18]. Diabetes was induced in Wistar rats and then administered with or without metformin (500 mg·kg -1 ·d -1 p.o.…”
Section: Effects Of Metformin On Glucose Insulin and Lipid Profilesmentioning
confidence: 99%
“…The mechanisms by which metformin improves glycemic control is mainly by reducing hepatic glucose production, and to a lesser extent, via enhancing peripheral insulin sensitivity, blocking gastrointestinal glucose absorption, modulating gut microbiota and promoting incretin axis (Ikeda et al 2000, Green et al 2006, Maida et al 2011, Miller et al 2013, Foretz et al 2014, Madiraju et al 2014, Shin et al 2014. In addition to its antidiabetic effects, metformin demonstrates multiple beneficial 'side effects' such as antiobesity, antihepatosteatotic and anti-inflammatory effects, and is currently in clinical trials to treat obesity (Malin & Kashyap 2014), NAFLD (Zheng et al 2015), polycystic ovary syndrome (PCOS) (Misso & Teede 2015) and certain types of cancer (Leone et al 2014, Morales & Morris 2015. Emerging evidence suggests that enhanced leptin sensitivity may contribute to the weight-loss effect of this drug (Aubert et al 2011, Malin & Kashyap 2014.…”
Section: Introductionmentioning
confidence: 99%